2019
DOI: 10.3390/polym11061071
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Polypyrrole Electrode into Piezoelectric PVDF Energy Harvester with Improved Adhesion and Over-Oxidation Resistance

Abstract: Smart textiles for wearable devices require flexibility and a lightweight, so in this study, a soft polypyrrole (PPy) electrode system was integrated into a piezoelectric polyvinylidenefluoride (PVDF) energy harvester. The PVDF energy harvester integrated with a PPy electrode had the piezoelectric output voltage of 4.24–4.56 V, while the PVDF energy harvester with an additional aluminum-foil electrode exhibited 2.57 V. Alkaline treatment and chemical vapor deposition with n-dodecyltrimethoxysilane (DTMS) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This adhesion creates a number of activation sites on PVDF surface. In this way, the current generated by the piezoelectric PVDF can flow in a more efficient manner, and the electrical conductivity of the electrodes is then crucial for the transferred current [44][45][46][47]. By increasing the temperature, figure 8(b), the generated power rises significantly because elevated temperatures increase the electrical conductivity as already shown in figure 4.…”
Section: Piezoelectric Property Of Pvdf-based Harvestermentioning
confidence: 82%
“…This adhesion creates a number of activation sites on PVDF surface. In this way, the current generated by the piezoelectric PVDF can flow in a more efficient manner, and the electrical conductivity of the electrodes is then crucial for the transferred current [44][45][46][47]. By increasing the temperature, figure 8(b), the generated power rises significantly because elevated temperatures increase the electrical conductivity as already shown in figure 4.…”
Section: Piezoelectric Property Of Pvdf-based Harvestermentioning
confidence: 82%
“…Today, the most accepted methods (Fig. 23) to modify the PVDF surface with various degrees of success are alkaline treatment [156,157], high energy ion irradiation [158][159][160][161], plasma treatment [148,[162][163][164], surface graft copolymerization [165], or combination of them [166]. As the above-mentioned literature, when the PVDF surface undergoes a surface modification treatment, generally two types of changes take place.…”
Section: Metal/pvdf Adhesion Strength Improvementmentioning
confidence: 99%
“…Among the many conductive polymers, PPy was used in wearable devices as electrode material because of its environmental stability and compatibility with living tissue. , However, major problems that still limit the application of PPy include the poor adhesion between PVDF and PPy. Fortunately, Baik et al succeeded at increasing the contact adhesion between PVDF and PPy using an alkaline treatment and chemical vapor deposition. The group showed that PVDF-based nanogenerators with PPy electrodes produce a higher output voltage (1.67 V) than PVDF-based nanogenerators with aluminum-foil electrodes.…”
Section: Suitable Flexible Materialsmentioning
confidence: 99%